Aspects of health literacy in the Roma population and the co-operation of nursing - Maňhalová, Jana; null, null; Rolantová, Lucie (STEF92 Technology Ltd., 2018)
Background: Recently, health literacy, in connection with trans-cultural problems and associated cultural competences, has become a hot topic of a number of specialties as a result of the globalized world, where the frontiers between individual states have become just imaginary lines on the map. The trans-cultural approach is closely associated with the individuals` integration in the society. The Romany, whose care of health has often been problematic, represent the most numerous minority in the Czech Republic that has never been a homogeneous society consisting only of one ethnic group. The aim of this paper is to present partial results of a study trying to identify health literacy in selected groups of South Bohemian population and, furthermore, to present the nursing possibilities with regard to the health literacy aspects of the Romany population living in the South Bohemian Region of the Czech Republic. Methodology: This paper presents partial results of the RVO ZSF JU project (Project of the South Bohemian University) called Health Literacy in Selected Groups of the Population of the South Bohemian Region, CR (SDZ16), which is being implemented between 2016 and 2019. The study is a quantitative survey preceded by a qualitative survey using the method of a semi-structured dialogue. The quantitative survey used the shortened form of HLSQ16 questionnaire (containing 16 items), which was developed to identify health literacy of the population. The data collection was performed in the target group of individuals who identify themselves as the Romany and who live in the South Bohemian Region. The respondents were chosen by the snowball method. Results: The results of a descriptive analysis revealed the mean score of 10, 22; therefore, it may be classified as the upper level of marginal health literacy, which ranks between 9 and 12 points. Based on the calculation of the health literacy index, using only respondents` complete answers (n=135), it was found out that inadequate, marginal and adequate health literacy had been found in 31.1%, 31.1% and 37.8% of the respondents, respectively. Conclusion: The Romany have marginal health literacy. The following question needs to be asked: Why does our society fail in trying to obtain adequate health literacy in the Romany minority and can somehow help nursing? The key barriers for Romany education include the Romany parents` experience with “special schools”, language barrier, separation of the Romany intelligentsia, disunity of the Romany minority, reduction of the Romany identity and other factors associated with the social exclusion and poverty.
Keywords: Health Literacy; Health; the Romany; Nursing; Nurse